Generalizations and analogical reasoning of junior high school viewed from Bruner's learning theory - Lilis Marina Angraini; Vahid Norouzi Larsari; Ilham Muhammad; Nia Kania (Jurnal Infinity, 2023)
Inductive reasoning has an important role in mathematics learning. It includes making generalizations and analogical reasoning. While a generalization explains the relationship between several concepts applied in more general situations, analogical reasoning compares two things. This research is qualitative and descriptive. It reviews and describes the mathematical reasoning abilities of junior high school students based on Bruner's learning theory. It was conducted at one of the junior high schools in Pekanbaru in the eighth grade in the 2022/2023 academic year, involving 70 students. The students were divided into three categories of prior mathematical knowledge: low, medium, and high. The instruments used to obtain data on how mathematical reasoning abilities relate to Bruner's learning theory in this study were (1) a test of mathematical reasoning abilities and 2) an interview guide. The results show that the average mathematical reasoning abilities of the eighth graders in this study were very high for the material on arithmetic sequences and series and low for the material on geometric sequences and series. However, the eight grade students' average generalizing and analogical reasoning abilities were quite good for both materials.